SEMIOTIC ANALYSIS "THE OLD MAN AND THE SEA" BY EARNEST HEMINGWAY - Salsa Billa Fauziah Tamami; Endang Susilowati (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2021)
This paper analyzed the novella entitled The Old Man and The Sea the work of Ernest Hemingway to find the meaning stored in the sign contained in the work by using semiotic theory which is a study of linguistic methods that only focuses on the meaning contained in the sign or symbol. With the theory used in Hemingway's literary work novella, several symbols were found, such as the symbol contained in the character Santiago himself, then the meaning contained in the number 84 symbol in the novella, then the meaning contained in the Marlin Fish symbol, and finally meaning stored in the symbol of the Shark that attacked Santiago's ship when he was about to return to the coast after spending days drifting in the middle of the sea with the big Marlin fish he caught.